Pengembangan Media Pembelajaran Interaktif Menggunakan Model Missouri Mathematics Project Untuk Meningkatkan Kemampuan Komunikasi Matematik Peserta Didik Di Kelas VIII SMP - Khairunnisa, Nurul Maulina; Yerizon, Yerizon; Suherman, Suherman; Arnawa, I Made (Universitas PGRI Madiun, 2022)
This research was motivated by the low mathematical communication skills of junior high school students. This study aims to produce Interactive Learning Media using a valid, practical, and effective Missouri Mathematics Project model to facilitate mathematical communication skills. This research is a development research carried out with the Plomp development model. The Plomp development model consists of three stages, namely preliminary investigation, prototyping stage, and assessment phase. This research was conducted at SMP Negeri 3. Data collection instruments in the form of interviews, documentation, questionnaires and test questions. The data obtained are analyzed by quantitative and qualitative data analysis techniques. The results showed that the interactive learning media for mathematics using the Missouri Mathematics Project model developed was classified as a very valid category (86.62% for RPP and 83.93% for media) and very practical at 87% and 86.85% respectively (for RPP and small group media) 88.1% and 88.02% (for RPP and large group media). Meanwhile, based on the test results of the mathematical communication ability test questions, 83.33% of students knew the criteria for the success of the mathematical communication ability test > 80%, meaning that interactive learning media using the Missouri Mathematics Project model was very effective on methematic communication skills